The Use of Gas Chromatography in the Analysis of Pharmaceutical Compounds: A Literature Review - Hasna Nisrina Huwaida Isfaizah; Mely Rosalinda; Salwa Roihana; Nadam Adi Reksa; Halyza Nada Kirana; Sayna Wahyu Ananta; Muhammad Ni’am Maulana (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: This review examines key advancements and applications of gas chromatography in pharmaceutical drug analysis by exploring innovations in instrumentation, sample-preparation strategies, and analytical performance across biological and non-biological matrices. The primary objective is to summarize recent progress in GC, GC-MS, and GC-MS/MS technologies and evaluate their effectiveness in detecting volatile and semi-volatile compounds, impurities, residual solvents, and degradation products. Method: A systematic search of indexed literature from 2015 to 2025 was performed using predefined inclusion criteria involving thematic relevance, completeness of data, and the direct application of GC methods. Result: Findings indicate that column selection, detector type, extraction approaches, and derivatization techniques markedly influence sensitivity, linearity, and quantification accuracy for analytes such as sibutramine, favipiravir, diclofenac, volatile anesthetics, cannabinoids, and phytochemicals. The discussion highlights that hybrid technologies, precise temperature programming, and optimized sample clean-up substantially enhance analytical performance. Conclusion: The review concludes that gas chromatography remains a critical analytical platform for pharmaceutical quality control and drug-stability evaluation across research and clinical settings.